2015
DOI: 10.1097/aud.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measurement in Adult Auditory Rehabilitation

Abstract: This review has highlighted considerable diversity in patient-reported outcome measurements in randomized control trials in the context of adult auditory rehabilitation. In addition, there are gaps in the literature with respect to measurement of other outcome types of potential interest to stakeholders, including policymakers and commissioners. Long-term outcome assessment is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Our review confirmed similar diversity (24 different tinnitus-related questionnaire instruments) and lack of consensus (14 used twice or more). In the second, Barker and et al [ 41 ] conducted a scoping review to document the range and nature of outcome measurement in the context of adult auditory rehabilitation. Like us, they included registered trials and published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review confirmed similar diversity (24 different tinnitus-related questionnaire instruments) and lack of consensus (14 used twice or more). In the second, Barker and et al [ 41 ] conducted a scoping review to document the range and nature of outcome measurement in the context of adult auditory rehabilitation. Like us, they included registered trials and published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the use of generic terms such as ‘handicap’ perpetuate the difficulty that many trialists experience in understanding what construct(s) are measured by a particular questionnaire instrument. The frequency of reporting adverse events was not given by Granberg et al [ 40 ], but Barker et al [ 41 ] stated that no studies reported on adverse events. Poor reporting of harms-related data is not restricted to clinical trials in the hearing sciences [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We know that studies using non-validated scales are prone to risk of bias [31]. In contrast, studies that use reliable, systematic and validated outcome measures give the possibility to compare different trials and perform a meta-analysis [32]. Another limitation is that the number of prospective randomized controlled trials in the field is low [22, 3336].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of usage of individual instruments is therefore low. This pattern of “many questionnaires in use, yet little consensus” (Granberg, Dahlstrom, et al., 2014) has been confirmed more recently by a scoping review (Barker, MacKenzie, Elliott, & de Lusignan, 2015). Some researchers have developed hearing loss assessment questionnaires that tap into specific domains, such as the social and emotional consequences of hearing loss that are in the HHIE.…”
Section: Introductionmentioning
confidence: 82%